“How Difficult English Is!” (An Attitude in Learning English for Non-English Students) - Nova Adi Kurniawan; Sai'in Sai'in (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2018)
English is one of the foreign languages taught from elementary to university. However, English is to be unswallowed bitter pill for non-English students. This is caused by the growing concepts of negative attitude about English, “English is frightening, English is hard to study, etc.” Attitude plays a vital role in learning any disciplines of knowledge includes English. Developing competencies and skills of English will not be achieved without noticing the supporting factors. In line with, this article discusses the concept of attitude, language attitude, students’ attitudes toward English, and the factors that influence students’ attitudes toward English as a foreign language.